Auto(trans)formação do pedagogo na cultura de convergência digital: novos processos a partir da epistemologia dialógico-afetiva - Favarin, Edenise do Amaral (2015)
This thesis, carried out at the Graduate Program in Education in the research line Formation, Knowledge and Professional Development, addresses educators' self (trans)formation in the culture of digital convergence from the perspective of a dialogical-affective epistemology. The overall objective is to investigate experiences of integration with digital technologies and the WEB in the Education major courses at the Federal University of Santa Maria. The specific objectives are to: a) characterize the new generation of pre-service teachers in the culture of convergence; b) examine official documents that support the Education major course in terms of its approximation to the concept of a culture of digital and technological convergence; c) map experiences of integration with digital technologies in Education majors; d) identify facilitating elements for integrating the culture of convergence and the dialogical-affective epistemology in Education majors. The methodological process involved the triangulation of information from the literature review, document analysis, an exploratory study using a Google Drive form and narrative reconstruction designed from the educational spiral approach. The theoretical conceptual definition was based on the concepts of teacher education, culture of digital convergence and the Education major program. The political-pedagogical project (PPP) of the undergraduate Education programs are aligned with official documents. However, the PPP offers few considerations regarding the digital culture as a curricular reference for the education of pre-service teachers. We infer that this shows a detachment from the culture of the new generation, which is an important aspect that is also highlighted in the Education major national curricular guidelines. In the Education major at UFSM, few teachers integrate technology into their teaching practices. Therefore, we believe that teachers need to overcome the fear of integrating digital technologies and the WEB to protagonize this paradigmatic rupture through their own conduct. Keywords: Teacher education. Culture of digital convergence. Education in the digital culture. Pedagogy in the digital culture